Restructuring and Performance: Efficiency Dynamics of Islamic Banks Before and After Spin-offs, Mergers, and Conversions - Hakim, Faqih Wildan; Rabaya, Abdullah Jihad; Ameraldo, Fedi; Rizki, Marsi Fella (al-Uqud : Journal of Islamic Economics, 2026)
The purpose of this research is to analyze the efficiency dynamics of Islamic banks following their separation, merger, and conversion. The study focuses specifically on changes in performance that occurred before and after these corporate restructuring procedures. Data Envelopment Analysis (DEA) and Hahslm Reflectivity Dynamics (HEFDYN) are employed in this work, which suggests that different restructuring models exhibit diverse patterns of efficiency. Generally, spin-off banks tend to experience a decline in efficiency after their operations are separated from those of the parent bank. Merger banks exhibit varied efficiency patterns, and converted banks display varying efficiency levels during the conversion process. The results of this study show the importance of policymakers and practitioners thoroughly evaluating the trade-offs between regulatory compliance and efficiency outcomes. This study adds to the discussions on the evolution of Islamic banking by providing empirical data on efficiency changes under various restructuring scenarios.